ChemInform Abstract: Direct C—H Arylations of Unactivated Arenes Catalyzed by Amido‐Functionalized Imidazolium Salts. Issue 33 (19th August 2014) - Ghosh, Debalina; Lee, Jhen‐Yi; Liu, Chian‐Yu; Chiang, Yen‐Hsin; Lee, Hon Man
Abstract An effective organocatalytic system based on an amido‐functionalized imidazolium salt allows the synthesis of biaryls from arylhalides and benzene.